An investigative case study of implementing a Transport Management System (TMS) with a rail freight network - Fagerberg, Andreas; Ungerth, David (My University, 2023)
This thesis examines the organizational prerequisites for implementing a Transport Management System (TMS) within Volvo Cars inbound logistics rail freight network. Volvo Cars is the largest automotive manufacturer in Sweden and their inbound lo- gistics operations handles hundreds of transports each day. By analyzing the case presented by Volvo Cars the study aims to provide answers to the following research questions: What actors, resources and activities are included in the rail freight net- work of this study? What information attributes are necessary for a successful TMS implementation of the rail freight network? What potential effects would a success- ful TMS implementation have on the rail freight network? The research provides a detailed map of all actors, resources and activities involved in the network as well as, a description of the rail freight process studied. The findings reveal that the centralized rail freight network studied is highly complex, primarily due to the number of actors involved and the facts that multiple systems that needs to be integrated to allow efficient communication. In addition to this, the structure of the network further contributes to the complexity of implementing a TMS since it demands a high degree of flexibility from the system. Through comprehensive analysis of the process, the critical information attributes for a successful implementation was identified and presented as well as additional information attributes that contribute value to the process but with less critical im- pact. Furthermore, the findings indicate numerous potential effects resulting from a successful implementation of the TMS. From the operational perspective, using a TMS would decrease the human errors and miss understandings due to inconsistent communication as well as, increase the pace of decision-making in time sensitive sit- uations. From the strategic perspective the generation of more data would lead to increased possibilities of improving and optimizing the process and provide a better general understanding of the rail freight network. The experience of implementing the TMS it would also benefit future rail freight initiatives of Volvo Cars.
Keywords: Transport management; rail freight; transport management system; system implementation; information attributes; information exchange